Concept of Rules “Alyakinu La Yuzalu Bisyaki” Create Independent Person - Kulsum, Umi; Fathan Al Kubro, Muhammad; Khasan, Abdullah (International Proceedings of Nusantara Raya, 2024)
The rule "Alyaqinu La Yuzalu Bisyaki" is a fundamental principle in the science of fiqh which emphasizes that beliefs that have been formed cannot be erased by doubt. This concept is not only relevant in the context of Islamic law, but also has significant implications in the formation of independent individual character. This research aims to explore how the application of this rule can shape individual attitudes and behavior in facing life's challenges. By emphasizing the importance of strong beliefs and overcoming doubts, individuals can develop a sense of self-confidence and independence in decision making. Through a qualitative approach, this study analyzes various psychological and social aspects related to these rules, as well as their impact on self-development. The research results show that understanding and applying the rules of "Alyaqinu La Yuzalu Bishyaki" can increase an individual's mental resilience and independence, thereby encouraging them to become more responsible and proactive individuals in everyday life. Thus, this rule is not only a guideline in a religious context, but also a basis for creating independent and competitive individuals.